Dlaczego mediacje - Kisielnicka, Maria (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article presents some theoretical aspects of mediation, discussing the differences in the types of mediation, and in particular those relating to criminal and civil cases, minors, family affairs, economic and cross-border issues. Attention is drawn to the importance of the development of mediation practice within the European Union. The author emphasizes the role of „restorative justice” and its importance for individuals, mentioning the considerably more prominent interest of citizens in concluding settlement agreements rather than in court decisions.
Keywords: sądy; sprawiedliwość naprawcza; mediacje; Unia Europejska